2022
DOI: 10.3390/soc13010012
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering: A Tool for Social Inclusion and Promoting the Well-Being of Refugees? A Qualitative Study

Abstract: Background: The Norwegian government’s increased expectations that volunteering can be used as a means of integration and the scarce research regarding refugees’ experiences with volunteering is taken as the background for this study. Our purpose is to adopt a salutogenic perspective to investigate whether and how formal volunteering contributes to developing a sense of social inclusion and well-being among refugees in Norway. Methods: Qualitative in-depth interviews were conducted with 12 volunteers with refu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Stated differently, the volunteerism model seeks to assist older adults to get better attention and care. Previous studies have documented that participation encourages the recognition [2] [4] [37] [45] [46] of ordinary persons as social actors who exercise agency in cognition and behaviour [45] [46] including appreciation [47] [48]. Sveen et al [2] also observed that volunteering can be used as a means of social integration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stated differently, the volunteerism model seeks to assist older adults to get better attention and care. Previous studies have documented that participation encourages the recognition [2] [4] [37] [45] [46] of ordinary persons as social actors who exercise agency in cognition and behaviour [45] [46] including appreciation [47] [48]. Sveen et al [2] also observed that volunteering can be used as a means of social integration.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence reveals that the voluntary sector should promote fellowship and provide the minority with the opportunity to contribute on an equal footing with the majority [1]. Sveen et al [2] have defined volunteering as a contribution, given freely, in an organized context without any expectation of a reward or other compensation to benefit individuals or groups outside the context of preexisting relationships (p. 1). According to Wilson [3], volunteering is a voluntary act of an individual or group freely giving time and labour for community service (p. 215).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Community volunteering also significantly helped supplementary immunisation activities (SIAs) for the polio disease in Sabah [ 4 ]. Some of the benefits of volunteering include community empowerment; increased resilience and social connectedness [ 5 ]; fostering a sense of communal trust, belonging [ 6 ], and support; and improving mental health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%